Analysis Of Irrigation Water Quality For Fields In Treman Village, North Minahasa Kauditan Regency - Salsabella, Syafira; Polii, Bobby; Rotinsulu, Wiske; Paat, Frangky; Porong, Jellie; Lumingkewas, Adeleyda; Luntungan, Jooudie; Wantasen, Sofia (EKOTON, 2022)
Abstract. Syafira Salsabella1), Bobby J. V. Polii1*), Wiske Ch. Rotinsulu1) , Frangky J. Paat1), Jellie V. Porong1) , Adeleyda M. W. Lumingkewas1), Jooudie N. Luntungan 2) , Sofia Wantasen. Analysis Of Irrigation Water Quality For Fields In Treman Village, North Minahasa Kauditan Regency. Ekoton   5. 28-35. This study aims to determine the quality of irrigation water in rice fields in Treman Village, Kauditan District, North Minahasa. This research was conducted for two (2) months, namely from March to April 2023. This research was conducted using purposive sampling method, the sampling technique is Composite. Research samples were taken at three points, namely the Primary Canal, Secondary Canal, and Tertiary Canal. Samples were taken as much as 4500 mL in each Canal, then analyzed at the Manado Industrial Research and Standardization Center Laboratory. The data obtained was analyzed using Bar Chart Statistics. The research shows that the Irrigation Water Quality of Rice Field Areas in Treman Village, Kauditan District, North Minahasa is still classified as very good because it meets the requirements as irrigation water according to Water Quality Of Irrigation based on Ayers & Westcott (1995), and there is no pollution based on Government Regulation No. 22 of 2021 concerning the Implementation of Protection and Management of Irrigation Water. Keywords: Quality of irrigation water, Sodium Absorption Ratio